I prodotti alimentari minori: chiocciole e rane Allevamento e specie commerciali, normative igienico-sanitarie e prospettive future. (Food In, 2015)
The heliciculture and frog breeding are zootechnic activities of great relevance that, actually, have not been taken in particular consideration overall by laws collected in the so named “Hygiene Package” because considered minor food or only food of niche. In fact, the presence of these meats on the market is still limited. The author wishes to underline the importance of nutritive value of snails and frogs meat and so the public can appreciate this alternative food by a correct consumer's information. One take in consideration not only the anatomic and physiologic aspects of these terrestrial gastropods and amphibians, but also the commercial species, the market in progress, the slaughter and the hygienic and sanitary and inspective aspects longer than the objective deficiency of rules.
Keywords: Heliciculture; Snail; Frog; Breeding; Alternative food; Amphibiculture